A novel regulator of ER Ca2+ drives Hippo-mediated tumorigenesis - Ma, Xianjue; Lu, Jin-Yu; Moraru, Alexandra; Teleman, Aurelio A.; Fang, Jinan; Qiu, Yue; Liu, Peng; Xu, Tian (Oncogene, 2020)
Calcium ion (Ca2+) is a versatile second messenger that regulates various cellular and physiological functions. However, the in vivo molecular mechanisms by which Ca2+ alterations contribute to tumor growth remain poorly explored. Here we show that Emei is a novel ER Ca2+ regulator that synergizes with RasV12 to induce tumor growth via JNK-mediated Hippo signaling. Emei disruption reduces ER Ca2+ level and subsequently leads to JNK activation and Hippo inactivation. Importantly, genetically increasing cytosolic Ca2+ concentration cooperates with RasV12 to drive tumor growth via inactivating the Hippo pathway. Finally, we identify POSH as a crucial link that bridges cytosolic Ca2+ alteration with JNK activation and Hippo-mediated tumor growth. Together, our findings provide a novel mechanism of tumor growth that acts through intracellular Ca2+ levels to modulate JNK-mediated Hippo signaling.
Published online: 24 October 2019
Im Titel ist "2+" hochgestellt
Gesehen am 24.06.2020